Kekerasan Seksual Terhadap Perempuan (Kajian Perbandingan Indonesia-India) - Yonna Beatrix Salamor; Anna Maria Salamor (Fakultas Hukum Universitas Pattimura, 2022)
Introduction: Violence that occurs against women today is an individual problem or a national problem, but it is a global and even transnational problem. This is because violence against women is related to human rights issues. Violence against women does not only accur in Indonesia. Almost in every country women face various types of violence. One of the most prominent countries with violence against women is India.Purposes of the Research: The purpose of this article is to find out about the comparison of sexual violence against women in Indonesia and India.Methods of the Research: The research method used is normative juridical research that uses legal sources of material obtained through literature studies and statutory regulations.Results of the Research: Sexual violence against women is not only a problem in Indonesia, but also a problem in various parts of the world. Cases of sexual violence against women that accur in Indonesia-India continue to increase. Therefore, cases of violence against women in Indonesia must be handled properly. One of them must have legal regulation as a basis for preventing sexual violence against women. In India it self already has regulations on sexual violence against women but the handling is not running effectively due to caste factors, economic factors.